2020
DOI: 10.1001/jamapsychiatry.2019.3986
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Outcomes of Cognitive Behavioral Therapy for Anxiety-Related Disorders

Abstract: IMPORTANCE Cognitive behavioral therapy is recommended for anxiety-related disorders, but evidence for its long-term outcome is limited. OBJECTIVE This systematic review and meta-analysis aimed to assess the long-term outcomes after cognitive behavioral therapy (compared with care as usual, relaxation, psychoeducation, pill placebo, supportive therapy, or waiting list) for anxiety disorders, posttraumatic stress disorder (PTSD), and obsessive-compulsive disorder (OCD). DATA SOURCES English-language publication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(135 citation statements)
references
References 61 publications
8
123
2
2
Order By: Relevance
“…Our results correspond well with previous shorter-term studies on the treatment of panic disorder and agoraphobia [2,4]and with the few studies reporting long-term outcomes [9,10]. Systematic exposure treatment and cognitive therapy yield substantial and lasting therapeutic gains, and these results can be achieved in the general clinical setting.…”
Section: Discussionsupporting
confidence: 90%
“…Our results correspond well with previous shorter-term studies on the treatment of panic disorder and agoraphobia [2,4]and with the few studies reporting long-term outcomes [9,10]. Systematic exposure treatment and cognitive therapy yield substantial and lasting therapeutic gains, and these results can be achieved in the general clinical setting.…”
Section: Discussionsupporting
confidence: 90%
“…Comprehensive reviews have shown that cognitive-behavioral therapy (CBT) is associated with surrogate measures of positive immune function: A reduction in pro-inflammatory cytokines, higher immune cell counts, natural killer cell activity, and immune outcomes [ 99 ]. CBT is a well-established intervention with long-term effects for a variety of psychiatric disorders such as major depression, generalized and social anxiety, or post-traumatic stress disorders [ 100 ]. In chronic pain conditions, systematic reviews have indicated a variety of small to moderate benefits in improving disability, catastrophizing, mood, and pain, though the significance is relevant to the study comparator (active treatment or treatment as usual) [ 101 ].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Response rates for exposure-based cognitive behavioral therapies are approximately 50% at posttreatment and 45% at follow-up (Loerinc et al, 2015). A recent meta-analysis of long-term outcomes in cognitive behavioral therapies for anxietyrelated disorders (including but not limited to exposure therapy) showed relapse rates after 3 to 12 months ranged from 0-14% (van Dis et al, 2019). Although there is little research that has systematically examined relapse rates following exposure therapy specifically, one study showed relapse in obsessive-compulsive disorder to be as high as 50% in treatment responders over the course of a typical follow-up period of 6 months (Hiss, Foa, & Kozak, 1994).…”
Section: Anxiety Disorders and Exposure Therapymentioning
confidence: 99%
“…Although there is little research that has systematically examined relapse rates following exposure therapy specifically, one study showed relapse in obsessive-compulsive disorder to be as high as 50% in treatment responders over the course of a typical follow-up period of 6 months (Hiss, Foa, & Kozak, 1994). A recent meta-analysis of long-term outcomes in cognitive behavioral therapies for anxietyrelated disorders (including but not limited to exposure therapy) showed relapse rates after 3 to 12 months ranged from 0-14% (van Dis et al, 2019). Although only six studies were included in the relapse rate analysis, these studies highlight the possibility of problematic relapse following anxiety disorder treatment.…”
Section: Anxiety Disorders and Exposure Therapymentioning
confidence: 99%